A Survey on Covid-19 & Its Impacts - Venkataramanan, A. R.; Kanimozhi, K. V.; Valarmathia, K.; Therasa, M.; Hemalatha, S.; Thangamani, M.; Gulati, Kamal (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In this survey paper, we have gathered nearly 30 papers to helps us in the identification of the new corona virus variant and the impact it has had. The global community has been traumatized by the Corona virus disease epidemic that originated in the end of the year 2019 that spread from China. The epidemic has overloaded advanced health care teams all around the world. WHO is actively looking into and reacting to this epidemic. The current statistical increase in the number of patients has prompted the use of AI approaches to foresee the probable result of a COVID affected patient that will benefit the heath care teams to make a decision on the manner of treatment to be administered. The intention is to find out whether machine learning-based algorithms can accurately compute whether or not Covid-19 recovery is achievable. We have analyzed papers that looked into the prediction of the new corona virus in suspected ill-patients, subject of vaccine acceptability, misuse of vaccine, effects of fake news among the community and repercussions that resulted in the usage of social media. This survey has assisted us in gathering a wide range of research information regarding Covid-19, its effects, and some of the treatment approaches proposed by other authors.